Membranous Nephropathy With Monoclonal IgM Lambda Deposits in a Patient With IgM Monoclonal Gammopathy: A Case Report - Hirose, Go; Uchida, Takahiro; Kojima, Aki; Sugisaki, Kentaro; Yamada, Muneharu; Nagase, Yoshihiro; Takaki, Takashi; Nagahama, Kiyotaka; Oda, Takashi (Frontiers in Medicine, 2021)
We report a case of membranous nephropathy with monoclonal immunoglobulin (Ig)M lambda deposits in a patient with IgM monoclonal gammopathy, in whom histological changes were observed on repeat renal biopsy. A 72-year-old Japanese woman was referred to our hospital because of massive proteinuria. A prominent increase in monoclonal IgM lambda level was identified, and she was diagnosed as having IgM monoclonal gammopathy of undetermined significance. Renal biopsy showed glomerular subepithelial electron-dense deposits that were found to be granular deposits of IgM lambda but not kappa or IgG by immunofluorescence staining, resulting in a diagnosis of membranous nephropathy with monoclonal IgM deposits. The second biopsy, which was performed 2 years later because of exacerbation of her nephrotic syndrome, demonstrated less immunofluorescence staining of IgM, and dominant IgG2 deposition without light chain restriction. Interestingly, immunostaining for thrombospondin-type-1-domain-containing-7A was positive in both renal biopsy tissues, although the second biopsy showed clearly stronger immunoreactivity. The effect of steroid therapy was limited; however, rituximab treatment improved both the hematological and renal abnormalities. Solitary deposition of IgM in membranous nephropathy is a quite rare condition. To our knowledge, this is the first case of monoclonal gammopathy of renal significance presenting as membranous nephropathy with monoclonal IgM deposits, in which chronological immunohistochemical changes were observed and rituximab therapy was effective.